Internationalization of soil physics from an American perspective - Kirkham, Mary B. (My University, 2013)
Upon the seventy-fifth anniversary of the Soil Science Society of America in 2011, a session was held at its annual meeting to document howthe field has changed over the years. I was asked to give the long-term perspective for soil physics. I surveyed soil-physics research published by the society over the past six years (2005-2011) and compared it with a review done in 1961 upon the twenty-fifth anniversary of the society. Of the 299 papers in my survey, 186 came from outside the USA (62% of the total). Twenty-nine countries were represented with the People’s Republic of China having the most papers (27 papers). In the 1961 review, only five countries outside the USA were cited. My survey showed that 48 papers (16%) dealt with water, 35 (12%) with mechanical properties, 19 (6%) with aeration, 18 (6%) with solute transport, 14 (5%) with repellency, and 10 (3%) with temperature. Of the non-USA papers in the survey, 27% gave no source of funding and the other 73% usually cited funding by the government of the corresponding author. Of the USA papers, 47% cited no source of funding. The results showed that soil-physics research has become heavily international.
Citation: Kirkham, M. “Internationalization of Soil Physics from an American Perspective.” International Agrophysics 26, no. 2 (April 1, 2012): 181–85. https://doi.org/10.2478/v10247-012-0026-6.
Keywords: Soil physics research; Internationalization; Funding of research